MOSQUES IN RURAL AREAS ARE A FORM OF CULTURAL ACCULTURATION IN INDONESIA. Case study: Mosques in Muntilan Village, Central Java, Indonesia - Pradipto, Eugenius; Wulansari, Maria Ariadne Dewi; Annisa, Natasha Nurul (Universitas Atma Jaya Yogyakarta, 2020)
Architectural form is a physical manifestation of culture as it acknowledges and responds the surrounding cultural context. Religious architecture also belongs into this principle. In Indonesia, the encounter between Islam coming from foreign Muslim merchants and the high culture of indigenous people fostered a process of cultural assimilation, which was also evident in the physical appearance of religious architecture products such as mosques. Demak Mosque, one of the earliest examples of this process, was completed during the period of nine pioneering Islamic scholars (Walisongo) c. 1401 AD and adopted the traditional tiered tajug roof from Pura (Balinese Hindu temple) and some other principles based on Hinduistic values. This paper set out to observe the process of cultural assimilation in form and construction of six mosques in the area of Muntilan, Central Java by comparing them to Masjid Demak, and to understand whether the alterations found in these mosques were done due to changes in religious values. The results show that most mosques have similar-looking exterior to Masjid Demak while there were increasing amount of alterations in newer mosques, mainly to improve the mosques’ functionality.